Combined Effect of Pore Water Overpressure, Far-Field Stresses, and Strength Parameters in Wellbore Stability - Deangeli, Chiara; Marchelli, Maddalena (Frontiers in Earth Science, 2022)
Studying the stability of wellbores drilled to access reservoirs can be a challenging issue in overpressured basins because accurate estimation of the far-field stresses, overpressure, and rock strength parameters can be difficult to achieve. Unexpected overpressures can induce tensile stresses around the wellbore, and the selection of an appropriate strength criterion and rock properties play an important role in determining the limit mud pressures. This study focuses on the stability analysis of wellbores by considering the mutual interaction of far-field stresses, fluid overpressure, and strength parameters of isotropic rock. We performed sensitivity analyses with the Mohr–Coulomb and Hoek–Brown criteria in two overpressured fields (North Sea basin and Browse basin) to highlight the influence of the uncertainties related to the rock strength. We defined an effective stress path (ESP) failure line to analyze the failure limit condition in the tension and compression zone. The analysis results indicated that the Hoek–Brown criterion better describes rock failure conditions, especially in the tension zone. Furthermore, we suggested using two different frictional components of strength for the tension and compression zone because it is a conservative approach, particularly at high overpressures. The mud pressures obtained from the uniaxial radial/tangential (HF) conventional analysis give different failure limits with respect to the ESP approach suggested in this study. These differences are low, and the mud weight margin can be low. In addition, we carried out numerical simulations with FLAC to investigate the extent of failure. The results indicated that the mud weight margin between the onset of local failure and borehole collapse is very low at high overpressures. Finally, the geomechanical analysis of wellbore stability in overpressured basins indicated the need for improving the accuracy in determining the strength parameters of the rock.